2019
DOI: 10.5811/westjem.2019.5.42096
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Informed Practice: Diagnostic Questions in Urinary Tract Infections in the Elderly

Abstract: An abnormal urinalysis in an elderly patient presenting to the emergency department (ED) with non-specific symptoms represents one condition that requires an evidence-informed approach to diagnosis and management of either asymptomatic bacteriuria or urinary tract infection (UTI). The emergency provider often will not have access to urine cultures, and the risks associated with antibiotic use in the elderly are not without potentially significant side effects. Methods: We performed a historical and clinical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…Urine culture had a high rate of contamination, which often led to repetitive urine culture. Contamination rates were significantly higher in cultures of midstream voided urine than in catheterized urine, in accord with a previous report [38]. This finding may also be related to patient age because 52% of these cases were aged over 60 years.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Urine culture had a high rate of contamination, which often led to repetitive urine culture. Contamination rates were significantly higher in cultures of midstream voided urine than in catheterized urine, in accord with a previous report [38]. This finding may also be related to patient age because 52% of these cases were aged over 60 years.…”
Section: Discussionsupporting
confidence: 90%
“…This finding may also be related to patient age because 52% of these cases were aged over 60 years. Most elderly patients have physical impairments that cause inherent difficulty in self-urine collection, therefore, more invasive collection methods are required to establish a reliable diagnosis [ 20 , 38 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have suggested that the APACHE II score could be used to effectively assess the severity of patients’ critical conditions and predict the mortality of severe patients admitted to intensive care units. [ 14 , 15 ] Moreover, the maximum theoretical score of APACHE II would be up to 71. The higher the score, the more serious the illness.…”
Section: Discussionmentioning
confidence: 99%
“…Urosepsis is the most common serious complication of urinary tract infection and is clinically characterized by occult onset, rapid progression, and poor prognosis. [ 1 , 2 ] If some patients suffering from it cannot be diagnosed as early as possible, their conditions would deteriorate rapidly, resulting in an increase in clinical mortality. [ 3 ] Urosepsis develops in 3 stages: systemic inflammatory response syndrome, sepsis, and septic shock each of which has a rate of clinical mortality that is apparently different from the others.…”
Section: Introductionmentioning
confidence: 99%
“…The use of PCT in the work-up of UTI has become of increasing interest to emergency medicine providers [ 20 , 45 ]. While PCT levels do correlate with bacteremia, C—reactive protein does not show any correlation with relevant clinical parameters in patients with febrile UTI [ 21 ].…”
Section: Discussionmentioning
confidence: 99%